LES PROJECTIONS DE PENSÉE NE SONT QUE DES FILMS QUE NOUS NOUS FAISONS SUR LES AUTRES ET QUI SONT LE PRODUIT DE NOS DIFFERENTS ENFERMEMENTS. RAPPORT SUR LE PROJET „PHILOSOPHIE VIVANTE” - Jean Jacques SARFATI (Studia Universitatis Babeș-Bolyai. Philosophia, 2023)
Thought Projections Are Nothing but Scenarios We Construct About Others and Are the Products of Our Own Closed-Mindedness. Report on the "Living Philosophy" Project. This text is a reflection on Projections. The aim here is to show that it is necessary to go beyond the Freudian concept to offer a more open reading of the concept of projections. The term is taken in its true sense. Projection is mainly used today in the world of cinema and entertainment. To be victim of a projection is to “make himself is proper film” of reality and live in an imaginary world. Our idea is to maintain that these projections develop in the era of the spectacle which is ours. The term “société du spectacle” is borrowed from Guy Debord. However, we distinguish ourselves from him by maintaining that the spectacle is only an epiphenomenon which is only the result of a culture of secret itself produced by contemporary narcissism. This work is the continuation of a series of conferences which are organized within the framework of a movement called Living Philosophy. This movement aims to bring philosophy back to life by leading it into living spaces and bringing it down into bodies, streets and villages. To do this, she wants to be creative and bring together the Ancients, the Moderns and the post-moderns. Living Philosophy is a movement built on the idea of dialogue and mediation.